Characteristics of simplified frequency-domain Volterra series based S-mode receiver - Fengxun GONG; Jiankun LI (Dianxin kexue)
The nonlinear characteristics of multilateration(MLAT) system were analyzed by simplified frequency-domain Volterra series when the S-mode signal response pulse was input.Firstly, take the typical super heterodyne receiver system for example, the model based on simplified frequency-domain Volterra series and error rate model of MLAT system were explored and created.Secondly, the S-mode response pulse signal model based on kernel function was researched and established.Finally, the model error rate of S-mode signal receiver system based on simplified frequency-domain Volterra series was analyzed when the S-mode signal based on kernel function was input.The results show that the minimum error rate of the receiver system based on 15 dB SNR simplified frequency-domain Volterra series is less than 23.23% when the S-mode signal based on kernel function is input.When the actual S-mode test signal with 16.25 dB SNR is input, the minimum error rate of the model is less than 22%, which is less than the error rate threshold.It shows that the receiver system model based on simplified frequency-domain Volterra series can accurately describe the characteristics of S-mode signal receiver system, which provides the theoretical foundation for the identification of preamble arrival timestamp in MLAT system.